Recent trends in income inequality - Hasell, J; Morelli, S; Roser, M (International Agency for Research on Cancer, 2019)
• In most advanced industrialized economies, within-country income inequality has risen since the 1980s after falling earlier in the 20th century. However, there were significant differences between countries in terms of the timing and extent of the rise. • Globally, the picture is much more complex, with recent falls in inequality in many high-inequality countries resulting in an average Gini index today that is quite similar to that of about 1990. • Significant rises in inequality since 1990 in several populous countries, including China, India, and the USA, mean that the average person lived in a country that had meaningful rises in inequality. • Given several concerns about data quality and interpretation, it is important to consider multiple perspectives on inequality. In particular, figures on top income shares that incorporate tax data and national accounts are a key complement to standard Gini index estimates based on survey data alone and, in some cases, present notably less benign trends in recent years.